Myocardial Injury in COVID-19 and Its Implications in Short- and Long-Term Outcomes - Izquierdo-Marquisá, Andrea; Cubero-Gallego, Hector; Aparisi, Álvaro; Vaquerizo, Beatriz; Ribas-Barquet, Núria (Frontiers in Cardiovascular Medicine, 2022)
COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global pandemic that continues to cause significant mortality and morbidity worldwide. Clinical manifestation varies from asymptomatic mild respiratory tract illness to severe pneumonia and death. Myocardial injury is one of the important pathogenic features of COVID-19 and it is associated with worse in-hospital outcomes with over 50% mortality. In addition, recent studies have shown that it is also associated with a worse 1-year prognosis, mainly due to a higher number of hospital readmissions. These findings suggest that myocardial injury would identify COVID-19 patients with higher risk during active infection and mid-term follow-up. Potential contributors responsible for myocardial damage are myocarditis, vasculitis, acute inflammation, type 1 and type 2 myocardial infarction. However, there is scarce information about the cardiac sequelae of this acute injury and its long-term consequences. Consequently, the optimal screening tool for residual cardiac sequelae, clinical follow-up, and the benefits of a specific cardiovascular therapy during the convalescent phase remains unknown. This mini-review explores the different mechanisms of myocardial injury related to COVID-19 and its short and long-term effects.